2018
DOI: 10.1146/annurev-med-050416-024516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the SPRINT Trial on Hypertension Management

Abstract: The Systolic Blood Pressure Intervention Trial is the first large prospective randomized controlled trial to demonstrate the benefit of an intensive systolic blood pressure (SBP) treatment target (<120 mm Hg) compared to a standard target (<140 mm Hg) in reducing cardiovascular morbidity and mortality and all-cause mortality in high-risk hypertensive patients. The impact of SPRINT on hypertension treatment has been large, but major questions remain about the feasibility of achieving the SPRINT intensive SBP ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Hypertension is a health disorder that affects a large part of the population worldwide. High blood pressure (BP) is considered the main risk factor for cardiovascular disease (CVD) [39]. Epidemiological studies have shown an association between hypertension, CVD and PD [40].…”
Section: Hypertension and Cardiovascular Diseasementioning
confidence: 99%
“…Hypertension is a health disorder that affects a large part of the population worldwide. High blood pressure (BP) is considered the main risk factor for cardiovascular disease (CVD) [39]. Epidemiological studies have shown an association between hypertension, CVD and PD [40].…”
Section: Hypertension and Cardiovascular Diseasementioning
confidence: 99%
“…The SPRINT and ACCORD clinical trials were two significant studies that shaped the most recent ACC/AHA guidelines. They, however, had certain limitations that may have affected their results: (1) The SPRINT trial showed a better cardiovascular outcome among the treatment group that received intensive treatment (aiming for systolic BP < 120 mmHg) compared with a standard treatment group (systolic BP < 140 mmHg), excluded individuals with end-stage chronic kidney disease (glomerular filtration rate < 20 mL/min/m 2 and proteinuria > 1 g/day), diabetes, and population in nursing homes or had dementia resulting in lack of generalizability (external validity) [ 14 ], and (2) The ACCORD BP trial revealed that tight BP control showed no advantage over standard therapy. However, many scholars felt the study was "underpowered" because of its design [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…Reducing diastolic BP below 60 mm Hg in those with CAD may magnify the risk of adverse cardiovascular events. The guidelines failed to address the issues of lowering diastolic BP [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…This study was motivated by increasing interest in understanding the relationships between BP and glaucoma, particularly because BP management guidelines have evolved in recent years. This is largely due to clinical trials such as the Systolic Blood Pressure Intervention Trial (SPRINT) [ 23 ], which showed that intensive systolic BP control to less than 120 mmHg was significantly beneficial to overall health. Some investigators have posited that intensive BP control may be specifically beneficial to glaucoma patients because a decrease in BP of 10 mmHg within five years led to a decrease in IOP [ 24 ], a known risk factor for glaucoma.…”
Section: Discussionmentioning
confidence: 99%